Optimal age selection for posterior hemivertebra resection and short fusion of a solitary simple lower thoracic or lumbar hemivertebra - Chuang Qian; Zhiqiang Zhang; Dong Fu; Junfeng Wang; Haodong Li; Yiming Zheng; Dahui Wang (BMC Surgery)
Abstract Hemivertebra (HV) is a leading cause of congenital scoliosis; however, the optimal timing for surgical intervention remains uncertain. This study aimed to compare surgical outcomes in children under 10 years old with scoliosis caused by a solitary simple lower thoracic or lumbar HV (T8–L5). From January 2015 to January 2024, we retrospectively analyzed 49 consecutive congenital scoliosis patients treated with posterior hemivertebra resection, fusion, and pedicle screw fixation. Of these, 35 patients met all inclusion criteria and were included in the final analysis. A minimum follow-up period of 12 months was maintained. We used ROC curve analysis to determine the age at which the rate of unplanned reoperation decreased, identifying a cutoff age of 5.07 years. Based on this criterion, we divided the pediatric population into two groups: the younger age group (≤ 5 years) and the older age group (> 5 years). No statistically significant differences were observed between the two groups in terms of correction rates in the coronal and sagittal planes. However, the unplanned reoperation rate was significantly higher in the younger age group (P = 0.016). Our findings suggest that delaying surgery until between five and ten years of age, combined with close follow-up, results in satisfactory outcomes with a lower rate of unplanned reoperation.